Non-axisymmetric dynamic response of imperfectly bonded buried orthotropic thin empty cylindrical shell due to incident compressional wave - Rajput R.S.; Kumar S.; Chaube A.; Dwivedi J.P. (My University, 2025)
This paper is deals with the non-axisymmetric dynamic response of imperfectly bonded buried orthotropic empty thin pipelines subjected to incident compressional wave (P-wave). In the thin shell theory the effect of shear deformation and rotary inertia is not considered. The pipeline has been modeled as an infinite cylindrical shell imperfectly bonded to surrounding. An approach similar to Dwivedi and Upadhyay (1989) has been followed wherein a thin layer is assumed between the shell and the surrounding medium (soil) such that this layer possesses the properties of stiffness and damping both. The degree of imperfection of the bond is varied by changing the stiffness and the damping parameters of this layer. Numerical results have been presented for the case of an incident plane longitudinal compressional wave (P-wave) only. The flexural mode (Non-axisymmetric) response has been discuss, it has been found that assumption of a perfect bond may not always lead to a safe and conservative estimate of the shell displacements and, hence consideration of the bond imperfection in non-axisymmetric mode response is necessary. © EuroJournals Publishing, Inc. 2010.